Serum Inflammatory Profile for the Discrimination of Clinical Subtypes in Parkinson's Disease - Yilmaz, Rezzak; Strafella, Antonio P.; Bernard, Alice; Schulte, Claudia; van den Heuvel, Lieneke; Schneiderhan-Marra, Nicole; Knorpp, Thomas; Joos, Thomas O.; Leypoldt, Frank; Geritz, Johanna; Hansen, Clint; Heinzel, Sebastian; et al. (Frontiers in Neurology, 2018)
Background: Blood levels of immune markers discriminate patients with Parkinson’s disease (PD) from controls. However, differences between clinical PD subgroups regarding these markers still need to be identified. Objective: To investigate whether clinical phenotypes can be predicted by the assessment of immune marker profiles in the serum of PD patients. Methods: Phenotypes of clinical PD from Tübingen, Germany (n=145) and Toronto, Canada (n=90) were defined regarding clinical subtype, disease onset, severity and progression as well as presence of cognitive and/or autonomic dysfunction. A panel of serum immune markers was assessed using principal component analysis (PCA) and regression models to define the marker(s) that were associated with clinical subtype after adjusting for potential confounders. Findings of both centers were compared for validation. Further, a [18F] FEPPA-PET was performed in a group of patients with high and low values of candidate markers for the assessment of in-vivo brain microglial activation. Results: Overall, serum immune markers did not cluster to define a pro/anti-inflammatory profile in PCA. Out of 25 markers only IL-12p40 showed a trend to discriminate between PD subgroups in both cohorts which could not be replicated by [18F] FEPPA-PET. Conclusions: Assessment of cytokines in serum does not reliably differentiate clinical PD subtypes. Accompanying subtype-irrelevant inflammation in PD, dual activity and lack of specificity of the immune markers, the complex function of microglia, probable effects of treatment, disease stage and progression on inflammation as well as current technical limitations may limit the usefulness of serum immune markers for the differentiation of subtypes.